Teachers’ knowledge about and perception towards learning disabilities in reading - Laguillo, Tamara; Cueli, Marisol; González-Castro, Paloma (Psychology, Society & Education, 2023)
Teachers play an essential role in the early detection and treatment of students with specific learning disabilities, hence the interest in assessing their knowledge and attitude towards this group of students. The aims of the current study were: to analyze differences in knowledge about specific learning disabilities of teachers from different educational profiles (Elementary Schools and Middle School teachers) and of teachers with different levels of experience with students with specific learning disabilities; and to examine teacher’s causal attributions of students with and without specific learning disabilities. Participants were 237 teachers, of whom 78.1% were women. Of the total 118 were elementary school teachers and 119 middle school teachers. All of them filled out the scale of knowledge about specific learning disabilities in Reading (38 items) which includes three dimensions (General Information, Symptoms/Diagnosis, Treatment) and the questionnaire of teachers’ casual attributions for students’ achievement (four items). Middle school teachers and teachers with lack experience with specific learning disabilities students displayed lower levels of knowledge of specific learning disabilities. Teachers substantially attribute students’ (with and without specific learning disabilities) achievement to intrinsic factors. In the case of failure, teacher’s causal attributions to external factors increased with specific learning disabilities students.